Metacaspases: Potential Drug Target Against Protozoan Parasites - Vandana,; Dixit, Rajnikant; Tiwari, Rajnarayan; Katyal, Anju; Pandey, Kailash C. (Frontiers in Pharmacology, 2019)
Among the numerous strategies/ targets for controlling infectious diseases, parasites derived proteases receive prime attention due to their essential contribution to parasite growth and development. Parasites produce a broad array of proteases which are crucial for processing of surface proteins required for parasite entry/ invasion, modification/degradation of host proteins for their nourishment and activation of inflammation that ensures their survival to maintain infection. Presently, extensive research is focussed on unique proteases termed as “Metacaspases” in relation to their versatile functions in plants and non-metazoans. Such unique metacaspases proteases could be considered as a potential drug target against parasites due to their absence in the human host. Metacaspases (MCAs) are cysteine proteases, having Cys-His catalytic dyad present in fungi, protozoa, and plants. Studies so far indicated that MCAs are broadly associated with apoptosis-like cell death, growth and stress regulation in different protozoa. The present review comprises the important research outcomes from our group and published literature, showing the role of metacaspases for therapeutic purpose against infectious diseases.